To solve the system of equations using the substitution method, we have the following equations:
- \(2x + 3y = 4\) (Equation 1)
- \(-4x - 6y = -8\) (Equation 2)
First, notice that Equation 2 can be simplified.
Step 1: Simplify the second equation
Dividing Equation 2 by -2 gives:
\[ 2x + 3y = 4 \]
Now we see that both equations are essentially the same, meaning that they represent the same line.
Step 2: Determine the type of solution
Since both equations are identical, they have infinite solutions. Any point (x, y) that satisfies \(2x + 3y = 4\) will also satisfy \(-4x - 6y = -8\).
Conclusion
The correct answer is infinite solutions.